Sonographic Evaluation of Effect of Smoking and Fatty Meals on Gallbladder - Kabir, Mohammad Ali; Kamal, Mahmud Hasan Mostofa; Hossain, ASM Shahidul (Journal of Enam Medical College, 2018)
Background: It is well established that fatty food causes gallbladder contraction by releasing cholecystokinin (CCK). Smoking also causes contraction of gallbladder. There are a limited number of studies evaluating the effect of smoking and fatty meals on gallbladder motility by ultrasonography. Objective: The aim of this study is to see the effect of smoking on gallbladder contraction in comparison with fatty meals. Materials and Methods: This cross sectional study was conducted on thirty young adult male volunteers having age between 18−40 years in the department of Radiology and Imaging of Bangabandhu Sheikh Mujib Medical University. Unbiased gallbladder volume measurement of each volunteer was taken on two separate days before and after taking fatty food and as well as before and after smoking at 5,15, 30 and 60 minutes interval. All information were meticulously recorded in structured data collection sheet and analyzed statistically. Then mean gallbladder volume changes against time were presented graphically for two groups using the pre and post smoking values. Results: The result shows that smoking has contractile effect on gallbladder like fatty food. The mean comparison of net change of gallbladder volume before and after smoking and before and after fatty food intake in both smoker and non-smoker groups has been statistically significant (p<0.05). Conclusion: Fatty food and smoking should be strictly prohibited before ultrasonography of hepatobiliary system for better evaluation. J Enam Med Col 2018; 8(1): 29-34